2018
DOI: 10.1080/20018525.2018.1536097
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, adverse events, and inter-drug comparison of mepolizumab and reslizumab anti-IL-5 treatments of severe asthma – a systematic review and meta-analysis

Abstract: Background: New, complex, and expensive therapies targeting Interleukin-5 (IL-5) to treat severe eosinophilic asthma are emerging.Objective: To assess efficacy, adverse events, and inter-drug comparison of mepolizumab and reslizumab for treating severe eosinophilic asthma.Design: A systematic review and meta-analysis on randomized, placebo-controlled, clinical trials elucidating two critical (exacerbation rate and oral corticosteroid (OCS) use) and six important clinical outcomes on the efficacy and safety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 36 publications
0
35
0
2
Order By: Relevance
“…12e14 A comparison of mepolizumab and reslizumab found no significant difference in any of the predefined clinical outcomes, including forced expiratory volume in 1 second (FEV 1 ), ACQ, AQLQ, annual exacerbations, and serious adverse events. 12 The authors noted that the quality of evidence was very low concerning interdrug difference comparison because there was substantial variability among the studies, including key differences in asthma severity and blood eosinophil level cutoffs. 12 The mepolizumab studies included patients with severe asthma based on GINA guidelines and an eosinophil cutoff of 150 to 300/mL, 12 whereas the reslizumab studies included patients with moderate asthma per GINA guidelines and an eosinophil cutoff of 400/mL.…”
Section: Comparative Biologic Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…12e14 A comparison of mepolizumab and reslizumab found no significant difference in any of the predefined clinical outcomes, including forced expiratory volume in 1 second (FEV 1 ), ACQ, AQLQ, annual exacerbations, and serious adverse events. 12 The authors noted that the quality of evidence was very low concerning interdrug difference comparison because there was substantial variability among the studies, including key differences in asthma severity and blood eosinophil level cutoffs. 12 The mepolizumab studies included patients with severe asthma based on GINA guidelines and an eosinophil cutoff of 150 to 300/mL, 12 whereas the reslizumab studies included patients with moderate asthma per GINA guidelines and an eosinophil cutoff of 400/mL.…”
Section: Comparative Biologic Effectivenessmentioning
confidence: 99%
“…12 The authors noted that the quality of evidence was very low concerning interdrug difference comparison because there was substantial variability among the studies, including key differences in asthma severity and blood eosinophil level cutoffs. 12 The mepolizumab studies included patients with severe asthma based on GINA guidelines and an eosinophil cutoff of 150 to 300/mL, 12 whereas the reslizumab studies included patients with moderate asthma per GINA guidelines and an eosinophil cutoff of 400/mL. 12 Unlike the aforementioned study, a separate network metaanalysis controlled for the heterogeneity between benralizumab and reslizumab studies by only selecting a benralizumab subgroup with a blood eosinophil count of 300/mL and a reslizumab subgroup with GINA step 4/5 or 2 previous exacerbations and an eosinophil count of 400/mL.…”
Section: Comparative Biologic Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, this means that these therapeutic strategies may not be sufficient to reverse remodeling changes of severe asthma even if mepolizumab has been shown to decrease the deposition of tenascin, lumican and collagen III in the basal membrane of mild atopic asthmatics as well as the degree of TGF-β in the bronchoalveolar lavage fluid [43]. Accordingly, lung function was not expected to be positively modified by anti-IL-5 treatments in severe asthma and a meta-analysis of nine randomized, placebo-controlled, clinical trials including mepolizumab or reslizumab reported a mild absolute difference of FEV1 in favor of the anti-IL-5 treatment compared to placebo [84].…”
Section: Treatment Of Severe Eosinophilic Asthmamentioning
confidence: 99%
“…A recent systematic review and meta-analysis revealed no differences between mepolizumab and reslizumab in terms of efficacy or safety measures 33 .…”
Section: B) Reslizumabmentioning
confidence: 99%